MENINGKATKAN SOLIDARITAS ANTAR TEMAN MELALUI BIMBINGAN KELOMPOK DI SD AL- MUTTAQIEN BOARDING SCHOOL SEMESTER GENAP TAHUN PEMBELAJARAN 2013/2014 - Arifin Nur Budiono (FKIP Universitas Islam Jember, 2014)
In order to be self-independet learners students are highly required to learn (Dimyati & Mudjiono, 2009: 5). According to Skiner (in Dimyati & MUdjiono, 2009: 9) learning is a behavior. He adds that when students are learning something, they will get better response. On the other hand, their response will decrease when they are not learning. In accordance with the previous illustration, the researchers conducted abservation in SD Al Muttaqien Boarding School Kaliwates. The result of the observation about students’ solidarity suggest tha it is between 55% -64%. This study aimed an investigating the e increase of students’ solidarity through the implementation of the group guidance. The researcher employs classroom action research (CAR) as a research method. It includes two cycles. The results of this study on cycle I suggest 80 % and on cycle 2 85 %. Based on the result of questionaire, the highest score for the “yes” answer is 23 or 92%. Further, for the “No” answer the result is 8 or 32%. Based on the previous result, it can perfectly prove that the students’ solidarity can be signivicantly improved through the implementation of this method. Keywords: Students’ solidarity, the group guidance